ANALYSIS OF GOOGLE CLASSROOM INTEGRATION IN TEACHING READING FROM THE STUDENTS’ PERCEPTION - Dwi Cahyo Saputro; Sri Handayani (English Education Department Slamet Riyadi University Surakarta, 2021)
The objectives of this research are: 1) To analyze the practices that were carried out in teaching and learning reading by using Google Classroom; 2) To analyze the students perceive the applications and the level of students’ perception towards the Google Classroom in teaching and learning reading; 3) To investigate the students’ behavior level towards the use of Google Classroom in teaching and learning reading. The subjects in this research were eighth-grade learners of State Junior High School 1 (SMP N 1) Colomadu. The students of 8A class, which had 32 students, were the subjects of this study. The research volunteers were chosen using a random sampling approach. The data was gathered by the researcher through observations at the school, interviews with the English teacher, and distribution of questionnaires to participants. The data collection approach is qualitative research, which involves data reduction, data display, and conclusion drawing and verification. According to the findings of this research, students at SMP N 1 Colomadu agree to the implementation of Google Classroom as an online platform for English learning. They believe that Google Classroom has helped them with all aspects of their learning. The integration of Google Classroom for SMP N 1 Colomadu was then successfully completed. Keyword: Analysis, Google Classroom, Teaching Reading, Perception